2010
DOI: 10.1002/jls.20164
|View full text |Cite
|
Sign up to set email alerts
|

Virtual communication, transformational leadership, and implicit leadership

Abstract: This research was designed to test the theoretical relationship among personality, implicit leadership, and transformational leadership in a setting devoid of face-to-face communication, which we entitled virtual communication. Specifically, the study was designed to link, by using the International Personality Item Pool (IPIP), traits from the 5-factor model of personality (the Big 5) to followers' perception of the leadership style of a virtual leader on the basis of Bass and Avolio's MLQ-5X (1994).A volunta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…MLQ is considered the full range leadership model for rating individuals' leadership behavior (Bass & Avolio, 2004). Salter, Green, Duncan, Berre, and Torti (2010) found that individuals associate motivational or inspirational words to a transformational leadership style. Subjects correlated effective communication to transformational leadership traits using MLQ to assess leadership behaviors (Salter et al, 2010).…”
Section: Multifactor Leadership Questionnaire Assessment Of Leadershimentioning
confidence: 99%
See 2 more Smart Citations
“…MLQ is considered the full range leadership model for rating individuals' leadership behavior (Bass & Avolio, 2004). Salter, Green, Duncan, Berre, and Torti (2010) found that individuals associate motivational or inspirational words to a transformational leadership style. Subjects correlated effective communication to transformational leadership traits using MLQ to assess leadership behaviors (Salter et al, 2010).…”
Section: Multifactor Leadership Questionnaire Assessment Of Leadershimentioning
confidence: 99%
“…Salter, Green, Duncan, Berre, and Torti (2010) found that individuals associate motivational or inspirational words to a transformational leadership style. Subjects correlated effective communication to transformational leadership traits using MLQ to assess leadership behaviors (Salter et al, 2010). Individuals in youth sports learned to associate key encouragement words to motivate teammates (i.e., the team believes in you) (Calhoun, 2007).…”
Section: Multifactor Leadership Questionnaire Assessment Of Leadershimentioning
confidence: 99%
See 1 more Smart Citation
“…45-item MLQ 5X has been widely used by researchers and scholars (Curtis, et al, 2017;Choi, et al, 2017;Yaghoubipoor, et al, 2013;Salter, et al, 2010;López-Zafra, et al, 2008). Previous research showed a reliability coefficient of .94.…”
Section: Questionnairesmentioning
confidence: 99%
“…Bass and Avolio's (1994) full range leadership model has led to continuous research regarding effects of leadership styles on employees' perception and performance (e.g. Hoyt and Blascovich, 2003;Judge and Piccolo, 2004;Lowe et al, 1996;Salter et al, 2010;Tejeda et al, 2001;Turner et al, 2002). As manifested by contemporary evidence (e.g.…”
Section: Transformational and Transactional Leadershipmentioning
confidence: 99%